In situ observation of the dissolution kinetics of Al2O3 particles in CaO-Al2O3-SiO2 slags using laser confocal scanning microscopy - Ren, Changyu; Huang, Caide; Zhang, Lifeng; Ren, Ying (International journal of minerals, metallurgy and materials, 2023)
The dissolution kinetics of Al 2 O 3 in CaO-Al 2 O 3 -SiO 2 slags was studied using a high-temperature confocal scanning laser microscope at 1773 to 1873 K. The results show that the controlling step during the Al 2 O 3 dissolution was the diffusion in molten slag. It was found that the dissolution curves of Al 2 O 3 particles were hardly agreed with the traditional boundary layer diffusion model with the increase of the CaO/Al 2 O 3 ratio of slag. A modified diffusion equation considering slag viscosity was developed to study the dissolution mechanism of Al 2 O 3 in slag. Diffusion coefficients of Al 2 O 3 in slag were calculated as 2.8 × 10 −10 to 4.1 × 10 −10 m 2 /s at the temperature of 1773–1873 K. The dissolution rate of Al 2 O 3 increased with higher temperature, CaO/Al 2 O 3 , and particle size. A new model was shown to be v Al 2 O 3 = 0.16 × r 0 1.58 × x 3.52 × ( T − T mp ) 1.11 to predict the dissolution rate and the total dissolution time of Al 2 O 3 inclusions with various sizes, where v Al 2 O 3 is the dissolution rate of Al 2 O 3 in volume, µm 3 /s; x is the value of CaO/Al 2 O 3 mass ratio; R 0 is the initial radius of Al 2 O 3 , µm; T is the temperature, K; T mp is the melting point of slag, K.